2014
DOI: 10.1007/s10822-014-9758-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into exosite binding and discovery of novel exosite inhibitors of botulinum neurotoxin serotype A through in silico screening

Abstract: Botulinum neurotoxin serotype A (BoNT/A) is the most lethal toxin among the Tier 1 Select Agents. Development of potent and selective small molecule inhibitors against BoNT/A zinc metalloprotease remains a challenging problem due to its exceptionally large substrate binding surface and conformational plasticity. The exosites of the catalytic domain of BoNT/A are intriguing alternative sites for small molecule intervention, but their suitability for inhibitor design remains largely unexplored. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…5. In corroboration with a previous computational study on lomofungin-BoNT/LC binding, 36 the key interaction of both molecules appears to be a hydrogen bond (H-bond) with the phenol OH of Tyr250. Furthermore, the conformation of the Tyr250 loop has been shown to be profoundly influenced by substrate binding to the LC; 35 therefore, a potentially stronger interaction of CBIP relative to lomofungin with Tyr250 may disrupt SNAP-25 binding, resulting in the superior inhibitory activity of CBIP.…”
supporting
confidence: 86%
“…5. In corroboration with a previous computational study on lomofungin-BoNT/LC binding, 36 the key interaction of both molecules appears to be a hydrogen bond (H-bond) with the phenol OH of Tyr250. Furthermore, the conformation of the Tyr250 loop has been shown to be profoundly influenced by substrate binding to the LC; 35 therefore, a potentially stronger interaction of CBIP relative to lomofungin with Tyr250 may disrupt SNAP-25 binding, resulting in the superior inhibitory activity of CBIP.…”
supporting
confidence: 86%
“…13 Clustering analysis of docking poses showed that the small molecule binds to the 7TM site of hRXFP1 in a similar manner as other agonists bound to different GPCRs. As shown in Figure 3, the core 2-acetamido-N-phenylbenzamide is accommodated in the typical ligand-binding pocket by forming extensive van der Waals and hydrophobic interactions with residues mainly from TM5 and TM7.…”
Section: Resultsmentioning
confidence: 96%
“…The binding mode of ML290 with the active RXFP1 was predicted using a step-wised ensemble-docking approach 13, 14 Ensembles of the active RXFP1 structure were generated from the MD simulations. A total of five cluster representatives were selected from the trajectory clustering analysis and used for the following docking study.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the CFP-YFP substrates were able to tolerate all of the tested human protein sequences; however, yields varied. In similar assays, substrates containing human protein sequences as long as 63 amino acids were successfully expressed, purified, and utilized for kinetic analyses and inhibitor screening 49,50,51 . Since only small amounts of the substrate are needed for the discontinuous assay, a large number of targets can be explored.…”
Section: Notementioning
confidence: 99%